رؤية مستقبلية لتحقيق الإصلاح الإداري لمؤسسات الرعاية الاجتماعية في مصر - محمد، محمود احمد إسماعيل (جامعة أسيوط - كلية الخدمة الاجتماعية, 2021)
يعد عدم التوجه نحو تطبيق الإصلاح الإداري من أكبر المشكلات التي تواجه الدول عالميا ومحليا، مشكلة مجتمعية كهذه وتواجه المسئولين خاصة وتؤثر عليهم سلبا، ولذلك كان من الواجب أن يكون لمهنتنا دور في مناقشة والمساهمة في حلها. كما تشكل الإصلاح الإداري بمؤسسات الرعاية الاجتماعية هدرا للموارد المستثمرة في إعداد وبناء الإنسان وتربيته وتعليمه وتدريبه وتأهيله للقيام بدوره الإداري بهذه المؤسسات. ولذا يهدف هذا البحث إلى تحديد واقع الإصلاح الإداري بمؤسسات الرعاية الاجتماعية، والوصول إلى رؤية مستقبلية لتفعيل لتفعيل وتطبيق الإصلاح الإداري بمؤسسات الرعاية الاجتماعية التي توجهت الدولة حاليا نحو تطبيقه. كما يهدف البحث إلى التوصل إلى أن الجودة والتطوير التنظيمي والتدريب تساهم في تحقيق الإصلاح الإداري بمؤسسات الرعاية الاجتماعية. كذلك مستوي أفضل لأبعاد تحقيق الإصلاح الإداري في مؤسسات الرعاية الاجتماعية ككل في إدارة الجودة الشاملة لتحقيق أفضل طريقة لتقديم الخدمة والقضاء على الروتين في العمل وتدعيم الترابط بين الإدارات. التطوير التنظيمي. تقييم الأداء للمسئولين لكي تتحسن الخدمات. التدريب للمسئولين لتحسين مستواهم الإداري.
Failure to implement administrative reform is one of the biggest problems facing countries globally and locally. It is a societal problem like this that faces officials in particular and affects them negatively, and therefore it was necessary for our profession to have a role in discussing and contributing to solving it. Administrative reform in social welfare institutions also constitutes a waste of invested resources. In preparing, building, educating, educating, training and qualifying people to carry out their administrative role in these institutions. Therefore, this research aims to define the reality of administrative reform in social care institutions, and to reach a future vision for activating and implementing administrative reform in social care institutions, which the state is currently heading towards implementing. The research also aims to conclude that quality, organizational development and training contribute to achieving administrative reform in social care institutions, as well as a better level of the dimensions of achieving administrative reform in social welfare institutions as a whole in total quality management to achieve the best way to provide service, eliminate red tape at work and strengthen interdependence between departments . Organizational development. Evaluating the performance of officials in order to improve services. Training for officials to improve their level of administration.
Keywords: الإصلاح الإداري -- مرسسات الرعاية الاجتماعية -- مصر